Development of Pop-Up Book Edutaiment Learning Media in Social Sciences Subjects - Barmadi, Muhammad Roy; Rahmi Novalita, Rahmi Novalita; Muharramsyah, Rambang (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This research aims to describe the practicality of Pop-Up-Book edutainment learning media in Social Sciences Subjects. The type of research is Research & Development (R&D) using the ADDIE model. The development subjects in this research were class VII students of state junior high school 1 Matangkuli, North Aceh Regency. Data collection techniques use observation sheets, questionnaires and documentation. The data analysis technique uses percentage analysis. The research results show that the practicality of Pop-Up-Book edutainment learning media is very practical. This can be seen based on the results of observations of learning activities, student learning activities, and the results of the Skills Process Assessment using the Edutaiment Pop-Up Book learning media.